2015
DOI: 10.1094/cchem-06-14-0139-r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nixtamalization Process on the Dietary Fiber Content, Starch Digestibility, and Antioxidant Capacity of Blue Maize Tortilla

Abstract: Cereal Chem. 92(3):265-270Nixtamalization is an ancient process developed by the Mesoamerican cultures. Initially, volcanic ashes were used and then calcium hydroxide in commercial production, and more recently nixtamalization with calcium salts (NCS) has been proposed. The aim of this study was to evaluate the effect of NCS on carbohydrate digestibility and antioxidant capacity in the elaboration of blue maize tortillas. NCS in blue tortillas showed a high amount of total dietary fiber (14.27 g/100 g), the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 50 publications
2
28
0
2
Order By: Relevance
“…However, this process decreases nutrients such as fat, protein, dietary fiber, and various nutraceutical compounds (Maya‐Cortés and others ). An ecological nixtamalization (EN) process patented by Figueroa and others () replaced lime used in the TN by calcium carbonate and demonstrated that the drawback of nutrient deterioration can be reduced (Bello‐Pérez and others ; Mariscal Moreno and others ; Santiago‐Ramos and others ). In addition, Mariscal‐Moreno and others () reported improvements in the nutrition profile of tortillas made with EN and classic nixtamalization (CN).…”
Section: Introductionmentioning
confidence: 99%
“…However, this process decreases nutrients such as fat, protein, dietary fiber, and various nutraceutical compounds (Maya‐Cortés and others ). An ecological nixtamalization (EN) process patented by Figueroa and others () replaced lime used in the TN by calcium carbonate and demonstrated that the drawback of nutrient deterioration can be reduced (Bello‐Pérez and others ; Mariscal Moreno and others ; Santiago‐Ramos and others ). In addition, Mariscal‐Moreno and others () reported improvements in the nutrition profile of tortillas made with EN and classic nixtamalization (CN).…”
Section: Introductionmentioning
confidence: 99%
“…In the traditional method, while most of the pericarp is disintegrated and passed into water, it remained in the ecological method. Bello‐Pérez et al () have reported less nutritional fiber loss happened in alkaline cooking made with calcium salts.…”
Section: Alkaline Cooking Methodsmentioning
confidence: 99%
“…Initially, wood ashes were used for the alkaline cooking process and then calcium hydroxide was started to be used in commercial production and recently an ecological cooking process was patented by Figueroa, Rodriguez‐Chong, and Véles‐Medina () in which calcium salt were used (e.g., calcium carbonate, calcium sulfate, and calcium chloride) (Bello‐Pérez, Flores‐Silva, Camelo‐Méndez, Paredes‐López, & Figueroa‐Cárdenas, ; Campechano‐Carrera et al, ). It is stated that the environmental effects of alkaline cooking with calcium salts are minimal (Bello‐Pérez et al, ).…”
Section: Alkaline Cooking Methodsmentioning
confidence: 99%
“…Total anthocyanin content was determined spectrophotometrically with the differential pH method and expressed as milligrams of cyanidin 3‐glucoside equivalents per 100 g of dry matter. Total phenolic content was determined by the Folin–Ciocalteu procedure and expressed as milligrams of gallic acid equivalents per gram of dry matter using a calibration curve .…”
Section: Methodsmentioning
confidence: 99%
“…Due to its appreciable phytochemical content, pigmented maize, mainly blue varieties, has been used to develop different functional foods, such as tortillas , chips , cereal bars , and cookies . Studies have suggested that these products have nutraceutical properties and have opened questions about possible interactions between carbohydrates and anthocyanins in pigmented maize.…”
Section: Introductionmentioning
confidence: 99%